2018
DOI: 10.1002/ldr.3118
|View full text |Cite
|
Sign up to set email alerts
|

Wind erosion enhanced by land use changes significantly reduces ecosystem carbon storage and carbon sequestration potentials in semiarid grasslands

Abstract: Wind erosion exerts a fundamental influence on the biotic and abiotic processes associated with ecosystem carbon (C) cycle. However, how wind erosion under different land use scenarios will affect ecosystem C balance and its capacity for future C sequestration is poorly quantified. Here, we simulated different intensities of land uses in Inner Mongolia: control, 50% of vegetation mowed (50 M), 100% vegetation mowed (100 M), and tillage (TI). We monitored abiotic C flux caused by wind erosion, net ecosystem exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 37 publications
1
38
0
Order By: Relevance
“…The C pool under the wind erosion scenario in CABLE model was calculated as Cpool=Cpool×sandc%+max(),0Cpool×()siltc%+clayc%Closs where sand c %, silt c %, and clay c % were contributions of organic C in sand, silt, and clay in soil surface to total SOC, respectively. Li et al () has indicated that contribution of organic C in fine fraction (<20 μm) to total SOC was 54.03%, and thus, silt c % plus clay c % was 54.03% and sand c % was 45.97% in this study.…”
Section: Methodssupporting
confidence: 59%
See 1 more Smart Citation
“…The C pool under the wind erosion scenario in CABLE model was calculated as Cpool=Cpool×sandc%+max(),0Cpool×()siltc%+clayc%Closs where sand c %, silt c %, and clay c % were contributions of organic C in sand, silt, and clay in soil surface to total SOC, respectively. Li et al () has indicated that contribution of organic C in fine fraction (<20 μm) to total SOC was 54.03%, and thus, silt c % plus clay c % was 54.03% and sand c % was 45.97% in this study.…”
Section: Methodssupporting
confidence: 59%
“…Thus, the soil organic N pool (N pool ) and soil mineral N pool (Nm pool ) under wind erosion scenario were expressed as Npool=Npool×sandn%+max(),0Npool×()siltn%+clayn%Nloss Nmpool=Nmpool×sandn%+max(),0Nmpool×()siltn%+clayn%Nmloss where sand n %, silt n %, and clay n % were the contributions of N in sand, silt, and clay in soil surface to total soil N, respectively. silt n % plus clay n % was 58.41%, and sand n % was 41.59% (Li et al, ). Given the N but not phosphorus (P) limitation on plant growth in the study region (Niu et al, ; Xia et al, ), P loss associated with wind erosion was not considered in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The frames were placed at least 2.5 m from the fence in deep‐snow treatment plots and in the corresponding direction and location in control plots. NEE was estimated from CO 2 flux rates under lighted conditions (see Li et al, 2018 for details). Ecosystem carbon (C) fluxes were measured three times a month throughout the growing season (May–September) from 2014 to 2018.…”
Section: Methodsmentioning
confidence: 99%
“…Accelerated erosion affects critical biotic and abiotic processes governing the soil/ecosystem C cycle. The magnitude of the loss of SOC by wind erosion is related to that of the fine soil fraction [43]. The loss of C-enriched fine soil particles depletes its SOC and reduces its future potential to restore the SOC pool.…”
Section: Wind Erosionmentioning
confidence: 99%